ESTETIKA ISLAM DALAM CERITA RAKYAT BANJAR: NISAN BERLUMUR DARAH - Agus Yulianto (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The aim of this research is to know about Islamic aesthetics described in Banjarese folktale, Nisan Berlumur Darah (Blood Covered Tombstone). The researcher chooses Islamic aesthetics in literary works, especially in Banjarese folktales as the topic of the study with consideration that there is still a little number of studies in this subject. Islamic aesthetics which are analyzed in this Banjarese folktale, Nisan Berlumur Darah (Blood Covered Tombstone), cannot be separated from the analysis of intrinsic element in literary work, those are characters and characterizations and mandate of the story as well. The research uses descriptive qualitative method. By analyzing the characters and characterizations and mandate of the story, one is able to know about Islamic aesthetic values in the story. The Islamic aesthetics are the height of knowledge and morals of the characters. Mandate in the story also be able to bear enlightening for the readers.